The prevalence of fatigue and the effectiveness of fatigue risk intervention on safety performance among shift workers in electronics manufacturing industry in Malaysia - Mohd Shahril, Abu Hanifah (2021)
Shift workers are exposed to fatigue at work because they tend to work longer hours and beyond their normal sleeping hours. Workplace fatigue can lead to decreased performance and quality of work and increased incidents at work. This study is conducted to examine the impact of shift work on workers’ fatigue, to assess the associated risk factors, and to identify its implication on safety performance among shift workers in selected electronics manufacturing industries in Malaysia. A fatigue risk management intervention was also developed and tested to observe its impact in reducing fatigue and improving safety performance among the shift workers. This study used a mixed-method approach that is divided into three phases. The first phase involved a cross-sectional study to look at fatigue levels and related risk factors using a set of questionnaires. Multidimensional Fatigue Inventory (MFI), Karolinska Sleepiness Score (KSS), Safety Attitude Questionnaire (SAQ), and Neal and Griffin Scale (NGS) were each used to determine fatigue, sleepiness, safety culture, and safety performance among the respondents respectively. The second phase focused on the development of a valid fatigue risk management intervention program using semi-structured interviews, workplace observations, and document reviews. The third phase used a quasi-experimental design (untreated control group pre-test post-test) to test the impact of the intervention on the respondents. This study revealed that shift workers in the selected electronics manufacturing industries experienced general fatigue (54.1%), physical fatigue (33.1%), mental fatigue (27.9%), reduced activity (22.8%), and reduced motivation (19.9%) during working hours. Factors such as gender, age, education level, monthly income, working experience, body mass index, sleeping on off-day, naptime, and quality of sleep were found to be significantly associated with fatigue among the respondents with an odd ratio (OR) range between 0.162 to 6.588. Structural equation modelling analysis indicated a significant negative relationship (b= -.30, S.E. = .06, p ) between fatigue and safety performance. The findings were used as a basis for the development, validation, and implementation of an intervention program in this study, which consists of a fatigue awareness training framework, fatigue risk management guideline, fatigue awareness training module, sitting exercise module, and awareness promotion materials. The intervention program has proven to be effective in reducing fatigue prevalence (12.0% to 21.6%) and further improve safety performance (9.2% to 10.7%) among the shift workers. This study suggests that shift workers who experience fatigue tend to have lower levels of safety performance and are more likely to be involved in incidents at work. However, a good understanding of the nature of fatigue occurrence in the workplace paired with a good commitment and cooperation between employers and employees could help to plan and to implement appropriate intervention strategies to properly manage the risk of acute and chronic fatigue.